Snail mucin is a functional food ingredient for skin. (May 2022) - Kim, Yongeun; Sim, Woo-Jin; Lee, Jeong-seok; Lim, Tae-Gyu
Graphical abstract: Highlights: Exposure to UVB is a primary reason for skin aging, including wrinkle formation, skin dryness, and loss of elasticity. Administration of snail mucin displayed anti-wrinkle activity by suppressing MMP-1/-13 expression with collagen restoration in mouse dorsal skin. Skin hydration activity of snail mucin intake was confirmed by preventing water loss. UVB-reduced skin elasticity was increased by oral administration of snail mucin in a dose-dependent manner. Abstract: Recently, the interests about functional ingredients for skin has been increased. Snail mucin has been used to as cosmetic constituent for skin though, the potential of snail mucin for nutricosmetic ingredient has not been fully evaluated. Mucin is a biosynthesized macromolecule which can protect the external damage. The present study investigated the photoprotective effect of the snail mucin against ultraviolet B (UVB)-induced skin photoaging in an animal model. SKH-1 hairless male mice were fed with snail mucin or vehicle for 14 weeks with UVB exposure. Evaluation for the skin damage was analyzed skin replicas, epidermal thickness and collagen fiber integrity, and the moisture contents in the dermal tissue. As well as we studied the effect of snail mucin on the expression of matrix metalloproteinase (MMP)-1/13, hyaluronic acid synthase (HAS) and hyaluronidase (HYAL). The safety of intake of snail mucin is also evaluated in the liver, spleen, and liver damage enzyme level. The results showed that the depth of the wrinkles, relative moisture content, relative elasticity induced by UVB irradiation on the epidermis of mice were obviously improved by supplementation of snail mucin. Furthermore, snail mucin intake did not cause liver size change, body weight change, spleen enlargement, and liver damage enzyme. Taken together, oral administration of snail mucin improved UVB-induced photoaging properties such as wrinkle depth, moisture loss, and loss of elasticity on the skin with no toxicity. Therefore, we suggest potential of ingredient of nutricosmetics.